Workforce Creativity Beyond Mood: A Strategic Framework of Vitality, Mindfulness, and Psychological Safety. - Karima, Billah Ahsanul; Parahyanti, Endang (Pertanika Journal of Social Sciences & Humanities, 2026)
Professionals are being pressurised to deliver unusual and helpful solutions within tight time constraints in the fast-moving creative economy. This paper explores the correlation of Proactive Vitality Management (PVM) with individual creativity, with the cross-level moderator of Psychological Safety (PS) and mindfulness as a mediating factor. Despite the fact that the role of PS and energy regulation as independent factors is well-established, empirical information about their combative, bottom-up effects in daily working environments is still limited. To fill this gap, a five-day diary study was conducted on 183 workers in the creative industries of Indonesia, including marketing, Information Technology (IT), and design. The experiment breaks down these interactions between these variables at various levels of inquiry by applying Multilevel Structural Equation Modelling (MSEM). The results showed that PVM significantly predicted both creativity and mindfulness. However, mindfulness did not mediate the relationship between PVM and creativity. PS moderated the relationship between PVM and mindfulness. At the within-person and between-person levels, PVM and PS consistently enhanced daily mindfulness and creativity, respectively. These results suggested the practical value of helping employees manage energy proactively and improving psychologically safe work environments to increase daily creative performance. The literature was enhanced by integrating proactive energy management and PS into a cross-level framework, offering new insights into the mechanisms required to improve workplace creativity.